Characteristic of typology of industrial heritage architecture from the 18th to the early 20th century in the Czech Republic - Fetisov, O. (Theory and practice of design, 2015)
The present research work deals with the problem of industrial heritage architecture in the Czech Republic. Historical objects of industrial architecture (industrial heritage architecture from the 18th to the early 20th century) and whole industrial areas are integral to the city environment nowadays. It is noted, that society has changed the approach for comprehension of industrial architecture typology at the beginning of the post-industrial period. As a result, the industrial architecture has forfeited the functionality. Most significant industrial buildings from the 18th to the early 20th century are іn devastated areas nowadays or objects with ineffective or inactive production. The methodology of present work assumes the analysis of general characteristics of industrial heritage architecture in the Czech Republic. The purpose of the present work is to identify and characterize the industrial heritage architecture from the 18th to the early 20th century in the Czech Republic according to the following criteria: functional characteristics, types of industry, size of the total area, location in the urban structure, number of floors, year of the construction, architectural style, arrangement and type of protection. The typical types of industry for industrial heritage architecture were selected from the Classification of Economic Activities (CZ-NACE). On the basis of results of the present research work the general conclusions have been developed.